(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The analysis of external and internal factors in the development of foreign trade activities of business entities showed unique results. In the organization and internal organization of foreign trade activities of business entities, collecting data and re-examining them creates a factor such as the attitude of an entrepreneur. Most of the problems are related to the legal and economic literacy of the entrepreneur, and it shows his attitude to social processes.